Numerical analysis of earth pressure of foundation pit adjacent to composite foundation. Issue 3 (May 2021) - Guo, Yuancheng; Gu, Shaochuang; Lv, Chenyu
Abstract: It is necessary to consider the influence of the surcharge load of the existing building and the displacement of the retaining structure when excavating the foundation pit adjacent to the existing composite foundation. FEM analysis work were conducted with two working conditions (condition of loading and condition of translation). The distribution and diffusion mechanism of lateral earth pressure acting on the retaining structure adjacent to composite foundation was investigated. It was found that, when there is no displacement of the retaining structure, the magnitude of additional lateral earth pressure acting on retaining structure adjacent to the natural ground and the composite foundation in the shallow area is almost the same. Moreover, compared with the natural ground, the composite foundation can block the horizontal diffusion of the load, resulting in the reduction of lateral earth pressure acting on the shallow area of retaining structure adjacent to the composite foundation is larger than that of adjacent to natural ground when retaining structure translation outwards.